The Effects of Enterococcus faecium and Selenium on Methotrexate Treatment in Rat Adjuvant-induced Arthritis - Jozef Rovenský; Karol vk; Vladimr Mat'ha; Richard Itok; Ladislav Ebringer; Miroslav Ferenčík; Mária StanĨková (Clinical and Developmental Immunology)
The effects of probiotic bacteria Enterococcus faecium (EF) and selenium were studied on methotrexate (MTX) treatment in rats with adjuvant arthritis (AA).